FEM modelling of the time-harmonic dynamical stress field problem for a pre-stressed plate-strip resting on a rigid foundation - Akbarov, S. D.; Yildiz, A.; Eroz, M. (ELSEVIER SCIENCE INC, 2011)
In this paper, the FEM modelling of the time-harmonic dynamical stress field problem for the pre-stressed plate-strip with finite length resting on a rigid foundation is developed. The mathematical formulation of the considered problem is made by the use of the equations and relations of the Three-dimensional Linearized Theory of Elastic Waves in Initially Stressed Bodies. The proposed modelling is tested on the concrete problems as an example. The numerical results testing the validity of the developed FEM modelling are presented. Moreover, the numerical results attained for the various values of the problem parameters are also presented. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Plate; Elastodynamics equations; Initial stress; Time-harmonic load; Forced vibration; Finite element method; WAVE-PROPAGATION; SLAB; ELEMENT; LAYER; Engineering; Mathematics; Mechanics